271 Assessment of Efficacy of Deworming Options in Recently Weaned Beef Cattle Utilizing Different Anthelmintic Programs in the Southeast. (8th October 2021) - Hernandez, Shane R; Davis, Dylan B; Tucker, Jennifer J; Credille, Brent; Stewart, R Lawton
Abstract: This experiment measured the effect of three different deworming strategies on animal performance and Egg per gram (EPG) reduction during a pre-conditioning phase of beef calves using a completely random block designed with n = 797 calves (Year 1 = 263 ± 39 kg; Year 2 = 257 ± 37 kg) randomly assigned to one of four treatments: orally suspended oxfendazole (1ml/55 kgs; ORAL), transdermal eprinomectin (1ml/10 kgs; POUR), both anthelmintic (BOTH), and no treatment (CONT). Weaned calves at four University of Georgia research stations (Calhoun, Alapaha, Eatonton, JPC) were blocked by weight, age, and sex. Calves were weighed at weaning prior to treatment d 0 and on d 42. Fecal samples were collected on d 0 and d 14 from 40 calves per treatment. Anthelmintic resistance was determined if percent EPG reduction and Upper 95% confidence limit were below 95% and the lower 95% confidence limit were below 90%. The ADG was lowest (P < 0.001) for CONT (0.262 kg/d) compared to POUR, ORAL, and BOTH (0.370, 0.412, and 0.387 kg/d, respectively) Anthelmintic resistance to POUR was detected at Eatonton and Alapaha (47.4% and 15.4% reduction respectively), and deemed inconclusive at JPC and Calhoun (51.1% and 50.3% reduction respectively). Only ORAL and BOTH effectively reduced EPG counts across all four research units (> 97.9% reduction). While the POUR option improved animal performance, it was not effective at reducing EPG within the herd. This study demonstrated that the ORAL and BOTH treatments increased ADG compared to CONT and were effective at reducing EPG counts; however, BOTH costs, on average, 3.00 more than ORAL. Producers must consider the cost of each option when choosing a deworming strategy. Based on these results, using orally suspended oxfendazole is a more economical, and effective options to treat parasites during a pre-conditioning phase.